Propriedades vibracionais da L-glutamina sob altas pressões e sob altas temperaturas - Holanda, Rocicler Oliveira (2010)
In this work, crystals of l-glutamine (C5H10N2O3) were subjected to analysis by Raman spectroscopy. Initially there was a identification attempt of all Raman bands and a second step we obtained the spectra of material ranging from the thermodynamic parameters of hydrostatic pressure and temperature. The spectral region for the experiments as a function of hydrostatic pressure was between 40 cm-1 and 3550 cm-1 and the variation of pressure between 0 GPa and 5.8 GPa. The results show that the crystal of l-glutamine undergoes a transition reversible structural phase around 3.0 GPa. Measures in function of temperature were made at two different biases in the spectral region between 30 cm-1 and 3600 cm-1 and in the temperature range between 20 °C and 140 °C. The results as a function of temperature does not provide evidence that the crystal of l-glutamine undergoes a transition phase or conformational changes in their molecules in the unit cell.